Viewpoints in Global Value Chains: Evidence from Sub-Saharan Africa - Bosire, Eric Mokwaro (International Journal of Economics and Financial Issues, 2023)
The aim of this paper is interrogate various perspective such as Investments, Infrastructure, Governance and Macroeconomic factors and how they influence global value chains in sub Saharan Africa. Data was derived from 37 sub Saharan Africa countries for the period 2003 to 2018. Panel corrected Standard Errors estimation model was adopted in analysis. Both the direct relationships and controlled relationships were tested. Macro-economic factors such as GDP growth rate, exchange rate, inflation rate and Interest rates were used as controlling factors. The paper established a significant influence of Investments on Global value chains and that it can explain up to 45 per cent of the variation. Similarly, infrastructure has a significant influence on global value chains in sub Saharan Africa and that it can explain up to 67 per cent of the variations. Governance also has a significant influence on global value chains and it can explain up to 10 per cent of the variations. The overall model was significant with a 76 per cent explanation of the variation in global value chains in sub Saharan Africa. Therefore, the paper recommends for a promotion of value added manufacturing, and an integration in global value chains. Further, the paper recommends for enhanced resource allocation to infrastructure development to aid in the reduction of the production cost and to stream line governance.